Survei Kreativitas Guru Penjaskes Dalam Menghadapi Pembelajaran Secara Daring di Sekolah Menengah Pertama - Aprilyadi, Aprilyadi; Usra, Meirizal; Yusfi, Herri (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2021)
This study aims to determine the creativity of sports and health physical education teachers in dealing with online learning in physical education subjects (PJOK). Creativity is needed in doing something like the learning process, in the learning process creativity is needed, a teacher who does not have creativity in teaching is unlikely to create creative and innovative students during the learning process. This type of research is a quantitative descriptive with percentage data and the method used is a survey method. The population of this study were all teachers of PJOK of State Junior High Schools in North Inderalaya District, Ogan Ilir Regency. Researchers took other subject teachers, principals and PJOK teachers with a total of 97 samples. Data collection techniques used are questionnaires and documentation. The data analysis technique used is statistical analysis of percentages in the form of frequency tables and histograms. Based on the research results obtained from the creativity of PJOK teachers in dealing with online learning, it is known that the percentage of PJOK teachers' creativity is 90,0% and for online learning 90,1% For the overall indicator of 90,2 %, the result means that it is included in the good category for the criteria for the percentage of teacher creativity in dealing with online learning.